Participation som kunst-værk - Heinrich, Falk (Peripeti, 2021)
The article asks whether participatory art radically alters the character of the work of art. This question is first explored through the concept of the aesthetic work of art that emerged during the aestheticism of the 19th century, and that is characterized by a stable and innately complete composition, before that concept is argued against with the opposing thesis that participatory works of art ‘need’ to construct a system or function frame that allows for participant agency in the concrete unfolding of the work. This framing must be able to, first, distinguish between elements (actions, objects, expressions, etc.) that either belong or not to a particular work of art and, second, support the participant’s perceptual interplay between material (inter)action and reflective observation.